Analisis Yuridis terhadap Implementasi Pasal 362 Kitab Undang-undang Hukum Pidana Tentang Pencurian pada Kasus Kendaraan Bermotor di Kota Batam - Kie Linten (Fakultas Hukum, Universitas Internasional Batam, 2017)
The purpose of this study is to analyze the implementation of article 362 of Criminal Code which conducted by law enforcement institution. This implementation analysis reviewed from regulation of enforcement law institution on vehicle’s robbery case. Due to uncooperation among enforcement law institution and other related state institutions such as Women Protection Commision, Children Protection Commision, Batam’s Major, Batam Indonesia Free Zone Authority (BIFZA) so as unefectiveness happended on avoidance of robbery case especially vehicle’s robbery in Batam city. Metedology used on this this research is empirical legal research which the secondary data obtained quantitatively to got a description of the main problem by using deductive thinking method. Primary data grouped based on variable research then analyzed quantitatively using statistic data formula so the clear description of main problems obtained. Data collection techniques are through field studies in the form of interviews and documentation studies. Thus, this analysis is defined through tables, graphs, and diagrams related to the problems studied. Bassed on this research can conclude: First, the implementation of article 362 of Criminal Code about vehicle’s robbery in Batam city has been implemented by the legal institution despite still not meet the legal efectivity yet. Second, the best solution to avoid vehicle’s robbery in Batam city are to increase the people welfare, consistency of legal enforcement and the availability of job oppurtunity for the poor people.